Swianiewicz, P. and Teles, F. (eds., 2018), Intermunicipal Cooperation in Europe. Institutions and Governance, New York, NY, Palgrave Macmillan. - Matteo Bocchino (Coordinamento SIBA, 2019)
For Book Reviews Abstract is not required